Cross‐resistance and baseline susceptibility of Mediterranean strains of Bemisia tabaci to cyantraniliprole. Issue 7 (15th September 2014) - Grávalos, Carolina; Fernández, Esther; Belando, Ana; Moreno, Inmaculada; Ros, Caridad; Bielza, Pablo
Abstract BACKGROUND The whitefly Bemisia tabaci Gennadius is a severe pest in many field and greenhouse crops worldwide and has developed resistance to insecticides from most chemical classes. The ease with which this pest develops resistance makes it essential to incorporate new compounds with different modes of action and no cross‐resistance with those previously used into insecticide resistance management strategies. To that end, the systemic effect of the new diamide cyantraniliprole was tested with multiresistant, selected and field populations of Q‐biotype B. tabaci from the Mediterranean area. RESULTS Bioassays with multiresistant and laboratory‐selected populations indicated no cross‐resistance to cyantraniliprole in the B. tabaci strains exhibiting resistance to other insecticides. The LC50 values for nymphs from 14 field populations varied between 0.011 and 0.116 mg L−1, a 10.5‐fold natural variability. The LC50 values for adults from three strains ranged from 0.060 to 0.096 mg L−1. CONCLUSION These baseline data will be helpful for monitoring future potential shifts in susceptibility to cyantraniliprole in Mediterranean whitefly populations within an IRM programme. Cyantraniliprole may play an important role in mitigating insecticide resistance in B. tabaci because of its high efficacy and its lack of cross‐resistance to other insecticides, even in multiresistant Q‐biotype populations collected from a highly problematic insecticide resistance area. © 2014 Society of Chemical Industry